Effect of official judo matches on handgrip strength and perceptual responses - Kons, Rafael Lima (J Exerc Rehabil, 2018)
This study aimed to verify the effect of judo matches on handgrip strength and perceptual responses during an official tournament in medalists and nonmedalists. Thirty-four male judo athletes participated in an official judo tournament. Before the first match and immediately after each match, maximum isometric handgrip strength and rate of perceived exertion overall and in specific areas were assessed. Analysis of variance for repeated measures was used to compare variables before the first match and after each match, and t-test was used to compare medalists and nonmedalists with the level of significance set at 5%. Also, effect size (ES) analysis was used. The results showed decrease in handgrip strength in both hands from the third match (P<0.05). The rate of perceived exertion (RPE) increased from the first match and remained high over the subsequent matches (P<0.001). A very large effect for nonmedalist group (ES=3.44) and large effect for medalist group (ES=1.94) was found in the third match compared to prematch. Forearm and fingers were the body regions most cited by athletes in both groups. We concluded that an official judo competition induced significant drop in handgrip strength from the third match and increased the RPE from first match. Medalists seem to have better recovery after the third match compared to nonmedalists.